Vstx1, a modifier of Kv channel gating, localizes to the interfacial region of lipid bilayers. - Bemporad, D; Sands, Z; Wee, C; Grottesi, A; Sansom, MS (2006)
VSTx1 is a tarantula venom toxin which binds to the archaebacterial voltage-gated potassium channel KvAP. VSTx1 is thought to access the voltage sensor domain of the channel via the lipid bilayer phase. In order to understand its mode of action and implications for the mechanism of channel activation, it is important to characterize the interactions of VSTx1 with lipid bilayers. Molecular dynamics (MD) simulations (for a total simulation time in excess of 0.2 micros) have been used to explore VSTx1 localization and interactions with zwitterionic (POPC) and with anionic (POPE/POPG) lipid bilayers. In particular, three series of MD simulations have been used to explore the net drift of VSTx1 relative to the center of a bilayer, starting from different locations of the toxin. The preferred location of the toxin is at the membrane/water interface. Although there are differences between POPC and POPE/POPG bilayers, in both cases the toxin forms favorable interactions at the interface, maximizing H-bonding to lipid headgroups and to water molecules while retaining interactions with the hydrophobic core of the bilayer. A 30 ns unrestrained simulation reveals dynamic partitioning of VSTx1 into the interface of a POPC bilayer. The preferential location of VSTx1 at the interface is discussed in the context of Kv channel gating models and provides support for a mode of action in which the toxin interacts with the Kv voltage sensor "paddle" formed by the S3 and S4 helices.